Opportunities for Brucellosis Control in Mexico: Views Based on the Sustainable Livelihoods Perspective - Oseguera Montiel, David; Frankena, Klaas; Udo, Henk; van der Zijpp, Akke (Frontiers in Veterinary Science, 2019)
Caprine brucellosis is a main constraint for small-scale goat husbandry systems in the Global South, as it negatively affects production parameters and can be transmitted to humans. The aim of this manuscript is to point out opportunities for brucellosis control in a resource poor area. The present paper draws from previous research in two Mexican states, Jalisco and Michoacán, both within the Bajío region. Main opportunities for brucellosis control are discussed within the “Sustainable Livelihoods Perspective.” Goat farming gives farmers a number of livelihoods benefits: food, cash, prestige, and a job. Goat farming is also a reason for some farmers to stay in their villages rather than to migrate to the US. This livelihood strategy, however, is threatened by brucellosis, which is endemic in the goat population of the region. Brucellosis control, however, offers an opportunity for small-scale goat farmers to enhance health and welfare. The socio-economic context is very important in planning a successful brucellosis control campaign. Control strategies should be planned considering the local goat farming husbandry and the views of the farmers.